Subjective modality as an anthropocentric attribute of a text and a linguistic personality - Radchuk, Olga; Tuchyna, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
Subjective modality is one of the leading textual categories, as singled out by contemporary researchers of the text categorial apparatus since it penetrates the whole text space and is the main constituent of the author’s image. The article aims to explore the category of subjective modality as one of the fundamental text categories that determines the specifics of all other categories in a fictional text. Various points of view as to the nature of the phenomenon of modality and the criteria for singling out its types are summarized. The two main types of modality – objective and subjective – are described in detail, though it is emphasized that the boundary between them is mostly conventional. The means of expressing modality are analyzed. The article focuses on subjective modality as a manifestation of the author’s world mapping in a fiction text and underlines that only subjective modality becomes a textual category. This type of modality gains even more importance within a framework of the anthropocentric paradigm, which is the leading one in modern philological research. The article also highlights the correlation between the category of subjective modality and the categories of evaluation and intentionality. The author’s attitude and intentions become clearer through it, making subjective modality the most essential text attribute. At the same time, its axiological orientation reflects fiction texts' pragmatics through using individual stylistic devices and other linguistic and literary expressive means. With the development of philological science and the separation of text linguistics into an independent scientific discipline, modality has also begun to be considered a category of text in recent decades. The study of subjective-modal factors in the text has enabled scientists to conclude that modality is a category, that it is inherent in the text, and that subjective modality is a universal category of the literary text.